Rola związków zawodowych w polskich przedsiębiorstwach (w kontekście wstąpienia do Unii Europejskiej) - Jasak, Agnieszka (The Role of Trade Unions in Polish Enterprises (in the Context of Poland's Accession to the European Union), 2005)
The study includes an attempt of analysis of the role of workers unions in enterprises. Some relations between social dialogue partners i.e. unions and employers were considered. Forms of agreements signed between partners of the dialogue were analyzed. Employees' ability of having influence on management decision taking process was considered as well. KGHM "Polska Miedź" SA was taken as an example of relationship between workers unions, management and the board of directors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 437-452